Analisis Sistem Manufakturing Prototipe Mesin Pengupas, Pemotong Dan Penggiling Bawang Merah Model Portable Multifungsi - Ulum, Miftahul; Putra, Farhan Wahyu; Gumelar, Naufal Rafif (Journal of System Engineering and Technological Innovation, 2023)
Shallots belong to one of the most widely grown agricultural commodities in Indonesia. However, to process shallots, there are several obstacles that can hinder their production, namely manual peeling and cutting processes. This has led to innovations to make a shallot peeling and cutting machine that is more effective and efficient in the production process. This study calculated the production rate and the production cost to find out how much the cost per unit is needed for the manufacture of the shallot peeler, cutter, and grinder machines. In addition, it employed the break-even point analysis to know whether it had sold enough units to cover all costs. After analyzing and performing calculations, the production time (Tp) was equal to 2,559.8 minutes/batch and the production rate was 0.0003 units/minute, or 0.43 units/day. The daily production capacity reached 17 units/month. Meanwhile, the 7 hours/batch and the net profit gained IDR 40,661,935/month. The Break-Event Point (BEP) was 0.48 units per month, and the sales (BEP) of the production achieved IDR 4,973,241 per month.calculation of Manufacturing Lead Time (MLT) obtained 11,502 minutes/batch = 191,7.